2016
DOI: 10.1210/jc.2016-1884
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion G Protein-Coupled Receptor G1 (ADGRG1/GPR56) and Pancreatic β-Cell Function

Abstract: We demonstrate a mechanistic link between ADGRG1 expression and β-cell function. Pharmacological agents that promote expression or activation of the ADGRG1 receptor may represent a novel approach for the treatment of T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 39 publications
9
69
0
Order By: Relevance
“…Since Gpr142 was abundantly expressed in β-cells with a marked impact on the GSIS, we performed Gpr142 -KD in INS-1832/13 cells and compared the expression level of Gpr142 to several other Gpcrs , i.e., Gpcrs with G q/o (Ffar1, Ffar2, and Ffar3) or Gpcrs with G s -coupling (Gpr56) reportedly impacting at least in part, different down-stream signaling pathway [9, 27]. As the release of cytokines was increased upon Gpr143 -KD, we also measured the expression of Tlr5 and Tlr7 two receptors involved in mediating inflammatory signals in pancreatic β-cells [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Gpr142 was abundantly expressed in β-cells with a marked impact on the GSIS, we performed Gpr142 -KD in INS-1832/13 cells and compared the expression level of Gpr142 to several other Gpcrs , i.e., Gpcrs with G q/o (Ffar1, Ffar2, and Ffar3) or Gpcrs with G s -coupling (Gpr56) reportedly impacting at least in part, different down-stream signaling pathway [9, 27]. As the release of cytokines was increased upon Gpr143 -KD, we also measured the expression of Tlr5 and Tlr7 two receptors involved in mediating inflammatory signals in pancreatic β-cells [33].…”
Section: Resultsmentioning
confidence: 99%
“…Gpr142 was downregulated in mouse islets using a cocktail of different Lenti-virus delivered shRNAs targeting the Gpr142 gene (sc-145707) (Santa Cruz, CA, USA) as we have described elsewhere for knockdown of other GPCRs [9, 39]. For downregulation of Gpr142 in rat INS-1832/13 cells, siRNAs (s180594) from Applied Biosystems (USA), with an appropriate scrambled control (4390846), were used according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of locally produced peptide ligands of islet GPCRs include glucagon and somatostatin, which act in a paracrine function to regulate secretion of islet hormones from neighbouring cells [2]. In addition, collagen III and IV, which are components of the extracellular matrix that supports islet cells, interact with the islet-expressed GPCRs, GPR56 and GPR126 [35]. GPCR peptide ligands that are delivered to islets in the circulation include the incretin hormones GLP-1 and GIP, which are secreted by specialised enteroendocrine cells in the gastrointestinal tract [6], and it has recently been reported that the cardiomyocyte-derived atrial natriuretic peptide stimulates insulin secretion via activation of β-cell guanylate cyclase-coupled GC-A receptors [7].…”
Section: Introductionmentioning
confidence: 99%
“…GPR56 does not appear to be required for survival of adult mammals since knockout mice are viable [25]. Although GPR56 may also interact with tissue collagen III and transglutaminase 2 [26, 27], specific ligands have not been identified and GPR56 has remained classified as an “orphan receptor” with unknown functions.…”
Section: Introductionmentioning
confidence: 99%